THE ROLE OF SOCIAL MEDIA IN CUSTOMER RELATIONSHIP MANAGEMENT AND BRAND IMAGE ENHANCEMENT - Shakira, Maulidia; Pebrianggara, Alshaf; Almanfaluti , Istian Kriya; Prasojo , Bayu Hari (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The times are gradually changing along with digitalization. Today, people are starting to use social media as a long-distance communication tool that is very influential in everyday life. With so many social media users today, social media is not only used as a means of social interaction. Changes in consumer behavior, which now more often rely on digital platforms, make social media can be used as a strategic tool in a business that can manage customer relationships and improve brand image. Method: Social media allows a business or company to communicate directly with consumers. Both businesses and companies can know and understand the needs and wants of customers and respond quickly if there are complaints or questions raised by customers. Results: With the right approach, this interaction can increase customer loyalty. In addition, it is also important to understand that social media allows businesses or companies to build and improve brand image through content that customers find interesting, interactive and relevant. Novelty: Social media can be used as a platform to convey their brand identity to a wider audience. An effective marketing strategy on social media can help create a positive impression, increase brand awareness and influence consumer purchasing decisions.